A Comparison of the Nulliparous-Term-Singleton-Vertex and Society of Maternal–Fetal Medicine Cesarean Birth Metrics Based on Hospital Size - Shields, Laurence E.; Walker, Suzan; Hedriana, Herman L.; Wiesner, Suzanne; Pelletreau, Barbara; Hitti, Jane; Benedetti, Thomas J. (American Journal of Perinatology, 2018)
Objective The purpose of this study was to compare the nulliparous-term-singleton-vertex (NTSV) and the Society of Maternal–Fetal Medicine (SMFM) cesarean birth metrics as tools for quality improvement efforts based on hospital size.Materials and Methods Cesarean birth rates from 275 hospitals from six states were used to evaluate the NTSV metric and 81 hospitals from four states for the SMFM metric. Data were assessed based on delivery volume, their use as an effective tool for ongoing quality improvement programs, and their ability to serve as performance-based payline indicators.Results The average NTSV and SMFM cesarean birth rates were 25.6 and 13.0%, respectively. The number of deliveries included in the NTSV metric was stable across all hospital sizes (33.1–36.2%). With the SMFM metric, there was a progressive decline in the number of deliveries included, 90.0 versus 69.6%, in relatively small to large facilities. Variability was less and precision increased with the SMFM metric, which reduced the number of hospitals that could be incorrectly categorized when using performance-based predefined cesarean birth rate paylines.Conclusion The SMFM metric appears to be better suited as a tool for rapid process improvement programs aimed at reducing cesarean birth rates in low-risk patients.
Keywords: cesarean section; Society of Maternal–Fetal Medicine; nulliparous-term-singleton-vertex; quality improvement